Decision support systems IX : main developments and future trends : 5th International Conference on Decision Support System Technology, EmC-ICDSST 2019, Funchal, Madeira, Portugal, May 27-29, 2019, Proceedings /: main developments and future trends : 5th International Conference on Decision Support System Technology, EmC-ICDSST 2019, Funchal, Madeira, Portugal, May 27-29, 2019, Proceedings. (2019) - Unknown
No abstract available